FROZEN SHOULDER: DOES HYDRODILATATION WITH STEROID HAS ADDED ADVANTAGE OVER INTRA-ARTICULAR STEROID INJECTION - CHOUDHARY, NITIN; GUPTA, SANJEEV (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: In our study, we will compare the efficacy of intra-articular steroid injection with hydrodilatation (with steroid) with regards to Shoulder Pain and Disability Index (SPADI), visual analog scale (VAS), and range of motion (ROM) in patients of adhesive capsulitis. Methods: The study is a prospective study carried out on 36 patients in Department of Orthopaedics, Government Medical College, Jammu, from August 2021 to July 2022. The patients were evaluated in terms of SPADI, VAS, and ROM (flexion, abduction, and external rotation) at 0-, 6-, 12-, and 24-week interval. Results: Hydro-dilatation has better results in comparison to intra-articular steroid injection. The patients with hydrodilatation fared with better scores in terms of SPADI as well as VAS with significant p-value (≤0.05). In addition, the patients also had better ROM in the former group. Conclusion: Hydrodilatation with corticosteroid provides better relief in terms of pain as well as ROM for frozen shoulder when compared to intra-articular CSI. The predictability of results with hydrodilatation is excellent and hence it is a better modality of treatment compared to intra-articular CSI.